Manajemen Wisata Budaya Berorientasi Pendidikan Pada Museum Asi Mbojo Bima Nusa Tenggara Barat - Susanti, Astuti; Ramli, Mauliadi (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the potential of the Asi Mbojo Museum and the strategy for developing the Asi Mbojo museum as educational and cultural tourism. To achieve this goal, the researchers used data collection techniques through interviews, observation and documentation. The data obtained from the research results were then processed using descriptive qualitative analysis. The results of the study show that the Asi Mbojo Museum has sufficient potential to be developed as an educational and cultural tourism object. These potentials include archeology, geology, biology, manuscripts, fine arts, collections of technology, cramonology, heraldics and numismatics. In addition, to increase the number of tourist visits, the Asi Mbojo Museum opens historical tours at the Bima Sultanate Mosque, Tolobali Cemetery, to the Taraha Fund, holds art performances, exhibitions, reviews of Bima history books and traditional activities of Tuha Ro Lanti (Coronation of Sultan and Jenateke or Crown Prince) and Hanta UA PUA. The strategy for developing the Asi Mbojo Museum as an educational and cultural tourism object is the SOBA ASI (Friend of Asi Mbojo) program. There are 5 activities in Soba Asi, namely the study of the history of Bima, historical and cultural studies, historical tours with benhur (benhur tours), courses on musical instruments and classical dance of the Bima palace and cultural arts performances.